Düşük doz lazer tedavisinin ve fotodinamik tedavinin oral mukozit üzerine etkilerinin karşılaştırılması / Comparison of the efficacy of low level laser therapy and photodynamic therapy on the effect of oral mucositis in rats - BAYER ALINCA, Suzan (Bezmialem Vakıf University, 2017)
Oral mucositis (OM) induces severe pain and limits fundamental life behaviors such as eating, drinking and talking for patients receiving chemotherapy or radiotherapy. In addition, through opportunistic microorganisms, OM frequently leads to systemic infection which then leads to prolonged hospitalization. Severe lesions often adversely affect curative effects in cancer cases. Therefore, the control of OM is important for oral health quality of life and prognosis. Low level Laser Therapy (LLLT) may be useful to accelerate wound healing. Indocyanine green can improve LLLT affect. In this study, 24 Sprague Dawley rats were divided into 3 groups as control, laser and laser+indocyanine green groups. All groups received 5-Fluorouracil intraperitonally and trauma to the mouth pouch with a needle. After the formation of OM in the mouth, the control group had no treatment; the laser group was administered laser, and the photodynamic therapy had LLLT after indocyanine green application. Then all groups were sacrificed and histologic and basic fibroblast growth factor (bFGF), transforming growth factor (TGF-β) and platelet-derived growth factor (PDGF-BB) were evaluated in all groups. LLLT with indocyanine green application was determined to be statistically significantly more effective than only laser application on bFGF and PDGF-BB groups. However, in respect of TGF-β, no statistically significant difference was observed between the groups. In conclusion, within the limitations of this study, indocyanine green can accelerate LLLT effect. However further studies on this subject are required.

{{abstract}}
Thesis (dentistry)--Bezmialem Vakıf University, Faculty of Dentistry, Department of Oral and Maxillofacial Surgery, Istanbul, 2017.
Keywords: Ağız mukozası = Mouth mucosa; Diyod lazer = Diode laser; Lazer tedavisi = Laser therapy; Ağız Diş ve Çene Cerrahisi Anabilim Dalı